Reinhabiting villages: the residential heritage of small towns between evaluation and prospects - Marina D'Aprile (Techne, 2022)
Small Italian villages, despite their significant variety , share the abundance of precious natural and cultural assets, the poor accessibility and the polycentrism that, historically, qualifies their settlements and a potential development process focused on the combination of innovation and tradition i.e. on the conservation and enhancement of their heritages. Scholars from different backgrounds have recently been emphasising the need to adopt integrated revitalisation policies in this regard, highlighting the role historic fabrics assume in their relationships – past, present and future – with contexts. Investigating the current state of studies on the subject, this paper highlights the instances, methods, purposes and limits of the approaches reserved for “residence” in this scenario, composing their possible critic appraisal.